2007
DOI: 10.1016/j.brainres.2006.11.088
|View full text |Cite
|
Sign up to set email alerts
|

The neural circuitry underlying the executive control of auditory spatial attention

Abstract: Although a fronto-parietal network has consistently been implicated in the control of visual spatial attention, the network that guides spatial attention in the auditory domain is not yet clearly understood. To investigate this issue, we measured brain activity using functional magnetic resonance imaging while participants performed a cued auditory spatial attention task. We found that cued orienting of auditory spatial attention activated a medial-superior distributed frontoparietal network, as well as audito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
123
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(145 citation statements)
references
References 64 publications
20
123
0
Order By: Relevance
“…This area of activation included primary and secondary auditory cortices (Brodmann areas 41 and 42) and extended into middle temporal cortices in both hemispheres. Combined with consistent results from recent ERP (Störmer et al, 2009) and neuroimaging (Wu et al, 2007) studies, this result shows that shifting attention to a spatial location in preparation for an expected auditory target leads to anticipatory pretarget biasing within auditory cortices. Third, the timing and sequence of attention-control activity in frontal and parietal regions were nearly identical to those found in a recent EEG study of visuospatial attention using similar methods .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This area of activation included primary and secondary auditory cortices (Brodmann areas 41 and 42) and extended into middle temporal cortices in both hemispheres. Combined with consistent results from recent ERP (Störmer et al, 2009) and neuroimaging (Wu et al, 2007) studies, this result shows that shifting attention to a spatial location in preparation for an expected auditory target leads to anticipatory pretarget biasing within auditory cortices. Third, the timing and sequence of attention-control activity in frontal and parietal regions were nearly identical to those found in a recent EEG study of visuospatial attention using similar methods .…”
Section: Discussionsupporting
confidence: 86%
“…Regardless of sensory modality, attentioncontrol activities were observed in both inferior and superior regions of the parietal and frontal cortices. Previous PET and fMRI studies have implicated these frontoparietal regions in the voluntary control of attention in vision (Corbetta et al, 2000;Corbetta and Shulman, 2002;Macaluso et al, 2003;Serences and Yantis, 2006), audition (Shomstein and Yantis, 2006;Wu et al, 2007;Salmi et al, 2009), and touch (Macaluso et al, 2002(Macaluso et al, , 2003, and in shifting attention between the visual and auditory modalities (modality selection) (Shomstein and Yantis, 2004). The similarities across modalities and tasks suggest that these frontal and parietal regions may perform general attention operations that are modality independent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is unclear whether the same frontoparietal regions are recruited for both auditory and visual tasks. Several studies have reported activity in a dorsal frontoparietal network that overlaps with the visual system during auditory stimulus anticipation, processing and attention shifts [Bharadwaj et al, 2014; Downar et al, 2000; Krumbholz et al, 2009; Langner et al, 2011; Lee et al, 2012; Linden et al, 1999; Mayer et al, 2006; Shomstein and Yantis, 2004; Watkins et al, 2007; Wu et al, 2007]. In contrast, there is increasing evidence that visual and auditory attention are subserved by different networks [Braga et al, 2013b; Bushara et al, 1999; Degerman et al, 2006; Kong et al, 2014; Maeder et al, 2001; Salmi et al, 2007; Seydell‐Greenwald et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of visual and auditory stimuli, the posterior parietal cortex is believed to synchronise the spiking activity in those neurons processing the attended stimulus enabling more effective attentional competition reflected by increased activity of the anterior insular cortex (Liu et al, 2003;Wu et al, 2007).…”
Section: Box 5 the Parietal And Insular Cortices And Attentional Commentioning
confidence: 99%